(untitled) (Revista Contexto & Educação, 2020)
This research aimed to analyze the training work of young musicians, developed by the Musical Society 15th of August in the city of Aliança, located in the Forest Zone of Pernambuco, based on Canclini’s theory of cultural hybridization (2015) and studies of sonorous landscapes by Schafer (2011). Thereby, it was sought to understand how hybridizations are present in the process of non-formal education of young people, collaborating in the construction of a musical production that is part of a contemporary local sonorous landscape under the influence of mass culture. The qualitative research was based on a combination of techniques such as bibliographical research, documentary analysis, and direct observation using a logbook and a semi-structured interview with the research subjects. Through the interpretation of the data in the light of the theories chosen as indicators, evidences of a hybridized musical production were observed, with young people as protagonists of the musical formation process. Futhermore, the entity’s participants identified through the testimonies, the presence of a hybrid sonorous landscape as part of a diversity of popular cultures that embody elements of the region and transnational mass culture.